ANALISIS KEMAMPUAN SISWA DALAM MENEMUKAN NILAI MORAL PADA CERITA RAKYAT JAWA GUNUNG TUGEL MATA PELAJARAN BAHASA JAWA KELAS IV MI TERPADU AL MABRUR TAWANGSARI SUKOHARJO TAHUN 2024/2025 - Rahmat, Basuki; Nurhidayati, Indah; Praptiningsih, P (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
Difficulty in comprehending Javanese, which has a rich vocabulary and many expressions, makes it challenging for students to find the moral values contained within the text. Therefore, the objective of this research is to determine the students' ability to find moral values and to identify the factors influencing their ability to do so in the Javanese folk tale,